A Systemic Capillary Leak Syndrome (Clarkson Syndrome) in a Patient with Chronic Lymphocytic Leukemia: A Case Report in an Out-of-Hospital Setting. (16th March 2016) - Durand Bechu, Manon; Rouget, Antoine; Recher, Christian; Azoulay, Elie; Bounes, Vincent
Abstract : Systemic Capillary Leak Syndrome (SCLS) is a rare disease with poor prognosis, characterized by the occurrence of mucocutaneous and visceral edema with hypotension, hemoconcentration, and unexpected hypoalbuminemia. The disease can be idiopathic (Clarkson syndrome) or secondary to other diseases and treatments. We describe this syndrome in a prehospitalized, 63-year-old patient with chronic lymphocytic leukemia and an idiopathic form of SCLS manifesting as hypovolemic shock. Initial care is hospitalization in intensive care. In addition to etiological treatment if fluid replacement is necessary, treatment must be closely monitored for secondary overload complications. Catecholamine rather than arrhythmogenic support may be associated.